2016
DOI: 10.1523/jneurosci.2712-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Direction Specificity in Visuomotor Learning

Abstract: The generalization of learning offers a unique window for investigating the nature of motor learning. Error-based motor learning reportedly cannot generalize to distant directions because the aftereffects are direction specific. This direction specificity is often regarded as evidence that motor adaptation is model-based learning, and is constrained by neuronal tuning characteristics in the primary motor cortices and the cerebellum. However, recent evidence indicates that motor adaptation also involves model-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Previous work has shown that learning a single gain perturbation at distal targets eliminates direction-specificity in rotation generalization, leading to rotation generalization across the entire workspace (Yin et al, 2016). It is unclear if this finding is consistent with a form of structural learning or a more general change in sensitivity to any form of visuomotor error.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that learning a single gain perturbation at distal targets eliminates direction-specificity in rotation generalization, leading to rotation generalization across the entire workspace (Yin et al, 2016). It is unclear if this finding is consistent with a form of structural learning or a more general change in sensitivity to any form of visuomotor error.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup had been used in our previous researches (Yin and Wei 2014; Wei et al 2014; Yin et al 2016; Jiang et al 2018). In all experiments, participants sat in front of a digitizing tablet and held the digital stylus with their left hand (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental setup had been used in our previous research (He et al 2016;Wei et al 2014;Yin and Wei 2014;Yin et al 2016). Participants sat in front of a table and slid their right index fingertips on the desktop (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesize that motor learning might show a similar directional effect if learning is critically dependent on the saliency of perceptual signals. To test our hypothesis, we examine the generalization of visuomotor rotation adaptation using savings as the learning metric (Krakauer et al 2005;Yin et al 2016). Savings refers to the phenomenon that relearning is faster than the initial learning.…”
Section: Introductionmentioning
confidence: 99%